The Syrian conflict and the distribution of hydrocarbons in the Middle East - Álvarez-Ossorio Alvariño, Ignacio (Política y Sociedad, 2018)
Syria has become a clear example of a failed state. The anti-authoritarian mobilizations of 2011 did not lead to the fall of Bashar al-Assad or the establishment of a democratic regime, but on the contrary the outbreak of a long and painful conflict. Since then, the situation on the ground has significantly worsened, not only as a result of the clash between the regime and the different opposition groups, but also by the intervention of regional and international actors. Nowadays, Syria is the scenario of a war by proxi among the United States, Russia, Iran, Saudi Arabia, Turkey and Qatar. The interference of these countries has caused the irruption of numerous militias with a clear sectarian agenda. The rivalry between Iran and Saudi Arabia for the regional hegemony has spreaded to the Syrian conflict, that has become a new scenario of the cold war between these regional powers. The Syrian war can not be understood without addressing the distribution of hydrocarbons in the Middle East and without referring to the regional projects to transport oil and gas from the Persian Gulf to Europe. Nowadays, the implementation of these projects is conditioned by the end of the Syrian conflict and the improvement of the security situation in the region.